2021
DOI: 10.5194/bg-2021-185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxygen export to the deep ocean following Labrador Sea Water formation

Abstract: Abstract. The Labrador Sea in the North Atlantic Ocean is one of the few regions globally where oxygen from the atmosphere can reach the deep ocean directly. This is the result of wintertime convection, which homogenizes the water column to a depth of up to 2000 m, and brings deep water undersaturated in oxygen into contact with the atmosphere. In this study, we analyze how the intense oxygen uptake during Labrador Sea Water (LSW) formation affects the properties of the outflowing deep western boundary current… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…While the main motivation for deploying these mooring arrays is to understand the AMOC's influence on Northern Hemisphere climate, the circulation system also plays a crucial role in distributing oxygen (O 2 ) and carbon dioxide (CO 2 ) throughout the global ocean. By adding O 2 sensors to several of the moorings at 53°N-60°N (Figure 1) in the western Labrador Sea, Koelling et al (2021) demonstrated that the formation of deep water, in which the AMOC brings surface water to the deep ocean, is important for supplying the oxygen consumed by deep-ocean ecosystems throughout the North Atlantic. Additionally, variability in the deep-water formation has been linked to changes in the amount of anthropogenic CO 2 stored in the subpolar ocean (Raimondi et al, 2021).…”
mentioning
confidence: 99%
“…While the main motivation for deploying these mooring arrays is to understand the AMOC's influence on Northern Hemisphere climate, the circulation system also plays a crucial role in distributing oxygen (O 2 ) and carbon dioxide (CO 2 ) throughout the global ocean. By adding O 2 sensors to several of the moorings at 53°N-60°N (Figure 1) in the western Labrador Sea, Koelling et al (2021) demonstrated that the formation of deep water, in which the AMOC brings surface water to the deep ocean, is important for supplying the oxygen consumed by deep-ocean ecosystems throughout the North Atlantic. Additionally, variability in the deep-water formation has been linked to changes in the amount of anthropogenic CO 2 stored in the subpolar ocean (Raimondi et al, 2021).…”
mentioning
confidence: 99%